Understanding teacher learning in lesson study through a cultural–historical activity theory lens. (November 2022) - Uffen, Iris; de Vries, Siebrich; Goei, Sui Lin; van Veen, Klaas; Verhoef, Nellie
Abstract: Although lesson study (LS) is widely considered a promising approach to teachers' professional development, the variation in teacher learning in LS is not yet well understood. Using a cultural–historical activity theory lens, we identify aspects of LS as a learning activity of significance for teacher learning. Using mixed-methods analysis of questionnaire and interview data drawn from 17 secondary school teachers, we find multiple variables of relevance in relation to teacher learning. This study clearly shows that participants' understanding of and attitude toward LS are at least as important as how LS is conducted.